Optimization of Cassegrain Systems Using Genetic Algorithms - Carlos Santos Rodríguez; Ana Teresa Aday Martínez (Revista Cubana de Ingeniería, 2012)
This paper is a proposal for optimization of a parabolic radiation system, in its variant Cassegrain, using Genetic Algorithms (GA). This new mathematical tool breaks through today in the field of electromagnetism, coming to be used as a successful way of solving problems of various antennas. In recent years there have appeared different softwares implementing the GA, this is the case of MATLAB 7.8.0. This software is used in this material to optimize a phenomenon that limits the good performance of the Cassegrain system, central blockage. The article is an attempt to introduce the use of the AG and its ability to multi-objective optimization of these systems, without any references of this topic in our country. It also uses reflectors analysis tool ICARA, which allows the simulation of radiation characteristics of different configurations of parabolic antennas for further analysis.